The land of the Pharaohs - Terzi, Marinella (Chicago : Childrens Press, 1992)
Examines the pyramids, temples, and other existing structures of ancient Egypt and discusses how they figured in or represent that civilization.
Translation of: El imperio de los faraones.
Includes index.
Keywords: Egypt -- Civilization -- To 332 B.C. -- Juvenile literature; Egypt -- Antiquities -- Juvenile literature; Egypt -- Civilization -- To 332 B.C.; Egypt -- Antiquities